Genetic variation in patent foramen ovale: a case-control genome-wide association study - Dong, Bosi; Li, Yajiao; Ai, Fandi; Geng, Jia; Tang, Ting; Peng, Wan; Tang, Yusha; Wang, Hui; Tian, Zixuan; Bu, Fengxiao; Chen, Lei (Frontiers in Genetics, 2025)
BackgroundPatent foramen ovale (PFO) is a congenital defect between the atria, resulting in abnormal hemodynamics. We conducted a genome-wide association study (GWAS) to identify common genetic variants associated with PFO.MethodsWe performed a whole genome sequencing in a discovery cohort of 3,227 unrelated Chinese participants screened for PFO via contrast transthoracic echocardiography (cTTE). Single-nucleotide polymorphisms (SNPs) associated with PFO were further validated by Sanger sequencing and subsequently were evaluated in a validation cohort. Expression quantitative trait loci (eQTL) analysis was conducted using the GTEx database. Single-cell sequencing analyses with pseudotime trajectory modeling were employed to evaluate their expression in human fetal hearts.ResultsThe case-control GWAS of discovery cohort ultimately included 517 cases and 517 demographically matched controls. Of the 7,040,407 variants assessed, we identified rs1227675732 (OR = 2.903; 95% CI, 1.961 to 4.297; p = 3.05 × 10−8), rs62206790 (OR = 2.780; 95% CI, 1.864 to 4.146; p = 2.02 × 10−7), rs879176184 (OR = 2.724; 95% CI, 1.822 to 4.073; p = 4.30 × 10−7) and rs13115019 (OR = 2.437; 95% CI, 1.702 to 3.488; p = 5.80 × 10−7) as high-risk variants for PFO, while rs57922961 (OR = 0.5081; 95% CI, 0.388 to 0.666; p = 6.82 × 10−7) was identified as protective variant. These variations were replicated in the validation cohort (111 cases and 152 controls). Single-cell sequencing showed that CNOT2, KCNMB4, MLLT10, IGBP1, and FRG1 were highly expressed with significant changes during heart development.ConclusionThe identification of susceptible loci for PFO might provide insights into the pathogenesis of PFO and contribute to understanding heart development.Clinical Trial Registrationhttps://www.chictr.org.cn/showproj.html?proj=40590, identifier ChiCTR1900024623.